Preconcentration and Determination of Chromium Species Using Octadecyl Silica Membrane Disks and Ammonium Pyrrolidine Dithiocarbamate - MOGHIMI, ALI (Asian Journal of Chemistry, 2010)
A novel and selective method for the fast determination of trace amounts of chromium species in water samples has been developed. The procedure is based on the selective formation of chromium ammonium pyrrolidine dithiocarbamate complexes at different pH in the presence of Mn(II) as an enhancement agent of chromium signals followed by elution with organic eluents and determination by atomic absorption spectrometry. The maximum capacity of the employed disks was found to be 402 ± 3 μg and 397 ± 2 μg for Cr(III) and Cr(VI), respectively. The detection limit of the proposed method is 52 and 46 ng L-1 for Cr(III) and Cr(VI), respectively. The proposed method was successfully applied for determination of chromium species Cr(III) and Cr(VI) in different water samples.